THE RIGHT TO FREE MEDICAL CARE IN UKRAINE AND FOREIGN COUNTRIES: ESSENCE, LIMITS, PROBLEMS OF IMPLEMENTATION - Sovgyria, O.V.; Yanchuk, A.A. (World of Medicine and Biology, 2018)
In connection with the implementation of modern medical reform, the increasing priority of social orientation of the state in the implementation of the policy by state authorities, there is an objective need for a comprehensive and integrated analysis of the issues of social rights and freedoms of man and citizen. The constituent group of rights is the right of everyone to health protection, medical care and medical insurance, provided for by Article 49 of the Constitution of Ukraine. Part 3 of this article of the Basic Law of Ukraine establishes that in state and municipal health care institutions medical care is provided free of charge. However, the modern realities of the health care system in Ukraine often indicate that the provision on free medical care in such health care institutions is the declarative norm of the Constitution of Ukraine, is not implemented in practice as a classic right (the latter presupposes the existence of the capabilities of the subject for which this right is fixed to implement it, the obligation of other subjects to create conditions for the realization of the right and not to hinder its implementation, as well as guarantees of the realization of the right and legal liability of entities infringing the right). The article examines the problems of legal regulation and implementation of provisions on free medical care in Ukraine, and also illustrates the model of providing such assistance on the example of European countries. Separately, the problems of providing free medical assistance to refugees and illegal migrants are highlighted and analyzed.
Keywords: the right to health care and medical care; free medical care